2019
DOI: 10.1016/j.knee.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Short term patient outcomes after total knee arthroplasty: Does the implant matter?

Abstract: Background-Newer implants for total knee arthroplasty (TKA) often gain market share at higher cost with little patient-reported and long-term clinical data. We compared outcomes after TKA using two different implants: Depuy PFC Sigma and Attune.Methods-Using a prospective data repository from an academic tertiary medical center, we analyzed 2116 TKAs (1603 Sigma and 513 Attune) from April 2011 through July 2016. Outcomes included length of surgery, length of stay, facility discharge, 90-day reoperation, range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…There was no relation between these radiolucencies and any of the migration profiles (translations, rotations, MTPM). Similar to other studies, 13 , 27 - 29 differences in the secondary outcome parameters such as clinical outcome and PROMS were not found, but the study was not powered for these parameters.…”
Section: Discussionsupporting
confidence: 72%
“…There was no relation between these radiolucencies and any of the migration profiles (translations, rotations, MTPM). Similar to other studies, 13 , 27 - 29 differences in the secondary outcome parameters such as clinical outcome and PROMS were not found, but the study was not powered for these parameters.…”
Section: Discussionsupporting
confidence: 72%
“…This is in accordance with the current studies with the largest cohort of patients; Molloy, Martin, and Ranawatt analysed respectively 2116, 1983, and 200 patients who undergone these two types of TKAs and failed to find any significant difference at functional scores [20][21][22][23]. Only a significant reduction of patellar crepitus and length of stay in hospital were seen in patients who underwent Attune TKA [20,22]. Discordant with these results are some minor studies with limited cohort of patients, which showed a little superiority of Attune TKA at functional scores [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…These authors even question the legitimacy of using a newer and costlier design in the absence of clear benefits. Another retrospective analysis by Molloy et al [8] demonstrated that Attune implants do not appear to improve ROM and physical function outcomes relative to PFC. The primary goal of the modification of a well-established implant should be an improvement of functional outcome and a decrease of unsatisfied patients.…”
Section: Discussionmentioning
confidence: 99%